GAMMA RAY-INDUCED MUTAGENESIS IN FORAGE CROPS: A BIBLIOMETRIC ANALYSIS - bela putra (Journal of Animal and Plant Sciences, 2025)
This research aims to provide a comprehensive overview of research focusing on inducing genetic mutations in forage crops, specifically green forage plants, using a bibliometric analysis approach. This bibliometric analysis used data from Scopus for the period 2010-2023. The keywords used in the search were "gamma AND ray AND forage OR mutation AND induction". Key elements of the analysis include publication trends, collaboration between institutions and countries, primary research topics, and keyword patterns. Findings; In terms of publication volume dynamics, the number of relevant studies initially rose significantly from 2010, followed by periodic fluctuations that reflect shifts in research priorities, funding availability, and global events impacting the field. Although there were phases of decline, the overall trend demonstrates sustained interest in gamma ray mutagenesis for forage crop improvement. Co-authorship analysis identified leading institutions, such as the Advanced Radiation Technology Institute and Zhejiang University, as key contributors with high research activity. Collaborations between these institutions and other international entities emphasize the importance of cross-institutional partnerships to address complex challenges and foster innovation in mutation breeding. Topic focus: Mutation induction, DNA repair, and radiation response emerged as the main research topics, reflecting a focus on harnessing gamma rays for genetic improvement and stress tolerance in forage crops. New research areas such as phenotype, genotype, and protein expression warrant further investigation. Keyword analysis: Keywords such as "article," "gamma radiation," "mutation," and "controlled study" highlighted the central themes and methodological rigor of research in this field. This bibliometric analysis provides valuable insights into the field’s research priorities and future directions. The study underscores the potential of gamma ray applications in forage improvement, though further research is essential to thoroughly assess the long-term benefits and risks. Continued collaborative efforts among researchers, policymakers, and stakeholders are crucial to ensure the sustainable advancement and application of this technology in the agricultural sector.
Keywords: Bibliometric analysis; Gamma ray; Induced mutation; Forage crops.